2023
DOI: 10.1002/hsr2.1153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotics resistance in Southern Iran in light of COVID‐19 pandemic: A retrospective observational study

Abstract: Background and Aims: Antimicrobial resistance (AMR) was taken as one of the highpriority long-lasting public health issues, although it might have been underrated in terms of COVID-19 pandemic emergence. Regarding limited data on assessing the pandemic effect on AMR trend in Iran, this study aimed to describe the epidemiology of antibiotics resistance during the COVID pandemic in southern Iran.Methods: This descriptive study was conducted on 2675 patients' samples collected and processed in a referral COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The significant increase in Gram-negative pathogens resistance to the antibiotics used in cases without other therapeutic resources, like colistin, as well as the increase in the number of PDR strains, are worrying elements for the future evolution of AMR [ 34 ]. These findings are consistent with other studies, reflecting the negative impact of COVID-19 on patients with MDR-Gram negative bloodstream infections and on AMR inside ICU settings [ 25 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The significant increase in Gram-negative pathogens resistance to the antibiotics used in cases without other therapeutic resources, like colistin, as well as the increase in the number of PDR strains, are worrying elements for the future evolution of AMR [ 34 ]. These findings are consistent with other studies, reflecting the negative impact of COVID-19 on patients with MDR-Gram negative bloodstream infections and on AMR inside ICU settings [ 25 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…against ceftazidime, colistin, and doxycycline, in the post-COVID-19 period compared to the pre-COVID-19 period. Another study, conducted in a COVID-19 referral hospital in Iran, showed a significant overall resistance increase among Gram-negative bacteria, particularly P. aeruginosa and K. pneumoniae [ 25 ]. A review conducted by Khaznadar et al also revealed that Gram-negative pathogens were those with levels of antimicrobial resistance most affected by the overuse of antibiotics during the pandemic [ 26 ], while a retrospective study conducted in Greece showed an increasing trend in the incidence of resistant Gram-negative bacteria, particularly in ICUs, compared to the pre-pandemic period [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Raoofi et al demonstrated the increase in AMR among Gram-negative bacteria in a retrospective observational study in Southern Iran. Particularly, the average change rate of PA (89%) and Klebsiella pneumonia (66.3%) resistance for the reported antibiotics was observed during the COVID-19 pandemic compared to the pre-pandemic [ 41 ]. Another retrospective study from April 2019 to April 2021, conducted in an adult ICU at the Hospital for Infectious and Tropical Diseases, Belgrade, Serbia, emerged as COVID-19 changed the landscape of HAIs (HAIs) in intensive care units (ICUs) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%